Analisis Putusan Hakim Nomor 16/Pdt.Sus-Desain Industri/2020/PN.Niaga.Jkt.Pst. antara Merek Geprek Bensu dan I Am Geprek Bensu - Nur Fauzia; Abdul Hariss (Universitas Batanghari Jambi, 2025)
Besides trademark, industrial designs are very valuable for every business actor in marketing, promoting and selling their goods and/or services to consumers. One of the industrial designs in the form of food packaging boxes functions as an identifier and marker for consumers. In this regard, each business actor is required to register their trademark and industrial designs with the Directorate General of Intellectual Property Rights of the Ministry of Law to avoid problems in the future. However, trademark and industrial design disputes cannot be avoided as the industrial design dispute that occurred between PT Ayam Geprek Benny Sujono and Ayam Geprek Ruben Samuel Onsu which resulted in a lawsuit at the Commercial Court at the Central Jakarta District Court with a ruling that canceled the industrial design registered in the name of Ruben Samuel Onsu. This scientific work examines the legal protection related to trademarks and industrial designs, the judge's considerations in canceling industrial design rights in the name of Ruben Samuel Onsu as stated in the Commercial Court Decision at the Commercial Court at the Central Jakarta District Court No. 16/Pdt.Sus Desain Industri/2020/PN.Niaga.Jkt.Pst and an analysis related to legal justice for the parties in the case related to the decision.